2006
DOI: 10.4049/jimmunol.176.8.5050
|View full text |Cite
|
Sign up to set email alerts
|

Substance P Stimulates Cyclooxygenase-2 and Prostaglandin E2 Expression through JAK-STAT Activation in Human Colonic Epithelial Cells

Abstract: Substance P (SP) via its neurokinin-1 receptor (NK-1R) regulates several gastrointestinal functions. We previously reported that NK-1R-mediated chloride secretion in the colon involves formation of PG. PGE2 biosynthesis is controlled by cyclooxygenase-1 (COX-1) and COX-2, whose induction involves the STATs. In this study, we examined whether SP stimulates PGE2 production and COX-2 expression in human nontransformed NCM460 colonocytes stably transfected with the human NK-1R (NCM460-NK-1R cells) and identified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 56 publications
(68 reference statements)
5
72
0
Order By: Relevance
“…It may play a role in JAK2 activation by IL-6, and this suggestion is supported by a previous report showing that rottlerin reduced the activation of JAK2 in NCM460-NK-1R cells [35]. However, we did not find any difference in JAK2 phosphorylation in the presence or absence of rottlerin (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…It may play a role in JAK2 activation by IL-6, and this suggestion is supported by a previous report showing that rottlerin reduced the activation of JAK2 in NCM460-NK-1R cells [35]. However, we did not find any difference in JAK2 phosphorylation in the presence or absence of rottlerin (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…The discrepancy may be due to the difference between two different cell types. Another independent pathway, JAK signaling which activates Stat3, has been shown to be involved in COX-2 expression [47]. Our studies also indicate that JAK signaling may participate in TP-mediated COX-2 expression.…”
Section: Discussionsupporting
confidence: 61%
“…We previously showed that SP-NK-1R interactions lead to Jak2 phosphorylation (27). Previous results also indicate that the signaling molecule PI3K is upstream of Akt signaling (28).…”
Section: Resultsmentioning
confidence: 99%
“…We also present evidence that Jak2 upstream of Akt is involved in this SP response. Interestingly, Jak2 was recently shown to also mediate cyclooxygenase 2 (COX-2) gene up-regulation and prostaglandin E 2 release in human colonocytes exposed to SP (27) and evidence was presented indicating that COX-2 promotes intestinal inflammatory responses (39). Thus, SP-induced Jak2 phosphorylation may mediate both proinflammatory and antiapoptotic signaling pathways.…”
Section: Discussionmentioning
confidence: 99%